2022
DOI: 10.12669/pjms.38.4.5093
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anxiety and depression in high school students of Karachi, Pakistan

Abstract: Objectives: Anxiety and depression are commonly occurring mental disorders in school-going students and if not considered can result in a worse outcome. The objective of our study was to determine the prevalence, risk factors and relationship of anxiety and depression with different variables among high school students of Karachi. Methods: This cross-sectional study was conducted in October - November 2020 in government and private high schools of four districts of Karachi. Two stage cluster sampling was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
2
4
1
Order By: Relevance
“…Our findings are consistent with another study, which also reported a higher prevalence among second-year students (Almigbal et al, 2022). According to a study by khan et al, the prevalence of depression was much higher among freshman medical students than it was among older students (Ibbad et al, 2022). In contrast, different research found that the risk of depression was considerably greater in third-year students compared to freshmen (Haykal et al, 2022).…”
Section: Resultssupporting
confidence: 92%
“…Our findings are consistent with another study, which also reported a higher prevalence among second-year students (Almigbal et al, 2022). According to a study by khan et al, the prevalence of depression was much higher among freshman medical students than it was among older students (Ibbad et al, 2022). In contrast, different research found that the risk of depression was considerably greater in third-year students compared to freshmen (Haykal et al, 2022).…”
Section: Resultssupporting
confidence: 92%
“…In the present study, the prevalence of anxiety symptoms among Afghan schoolgirls was 65.5%. A similar prevalence of anxiety has been reported in studies conducted among university students in Pakistan (53.2%) (30), and a systematic review in Iran (6.8%-85.0%) (31). Compared to the present study, a lower prevalence of anxiety was reported in studies conducted among school students in Egypt (6.7%) (32), Malaysia (39.7%) (33), and India (17.9%) (34), France (32.7%) (35), South Africa (32.0%) (36), Nigeria (10.3%) (37), China (24.8%) (38), Portugal (6.5%) (39), UAE (28.0%) (40), Sri Lanka (28.0%) (41), Bangladesh (18.1%) (42), Saudi Arabia (34.2%-65.0%) (43), and Turkey (42.0%) (44).…”
Section: Discussionsupporting
confidence: 78%
“…A recent study conducted in Pakistan, on 400 high school going adolescents (15-18 years), identified the prevalence of anxiety and depression around 53% in Pakistan. 5 The rates of anxiety and depression among adolescent population are alarming in the context of Pakistan where the mental health human resources are scare. There are only few child and adolescents psychiatrists, and hardly any specialized mental health nurses and formalized mental health services for children and adolescents in Pakistan that can be considered at par with the developed world.…”
Section: Lubna Ghazalmentioning
confidence: 99%